Evaluation of the New Student Admission System Service Program in Improving Educational Quality at SMA Negeri 5 Sekadau Hilir Using the CIPP Model - Maria Emakulata; Afandi Afandi; Eni Rosnija; Eny Enawaty; Henny Sanulita (FKIP - Universitas Riau, 2026)
The student admission system is a strategic instrument for ensuring equitable access and improving the quality of education; however, its implementation often remains administratively oriented and does not fully support sustainable quality management. This study aims to evaluate the student admission service system by examining policy alignment, resource readiness, service process quality, and its implications for educational quality. The research employs a qualitative approach with an evaluative design based on the Context, Input, Process, and Product (CIPP) model. Data were collected through semi-structured interviews, observation of service processes, and document analysis, and were analyzed interactively through data reduction, categorization, and interpretation of findings. The results indicate gaps between policy objectives and operational implementation, limitations in supporting inputs, service processes that remain largely procedural, and suboptimal use of admission outcomes for quality planning. The discussion emphasizes that student admission services need to be reoriented from merely an administrative selection mechanism to a strategic instrument for improving educational quality. This study concludes that the CIPP model is effective as a comprehensive evaluation framework to support data-driven decision-making and continuous improvement in educational management.